Nursing care for patients with Guillain-Barré Syndrome: a systematic review of the literature (Research, Society and Development, 2023)
Objective: To synthesize through review of research conducted on nursing care to patients with Guillain-Barré Syndrome (GBS), along with a systematized assistance. Method: A systematic literature review study was carried out, which provided a synthesis of knowledge and an approach to nursing care for patients with GBS. For the search of the publications used the following databases: The Virtual Health Library (BVS), Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (SCIELO), Google Academic, PUBMED and MEDLINE, filtered through the following descriptors in health sciences (DeCS): 'Guillain-Barré Syndrome', 'Nursing care', 'Treatment' and 'Rehabilitation'. The inclusion criteria used were: publications that matched the proposed theme, associated with the Portuguese and English languages, delimited between the years 2007 and 2022. The exclusion criteria used were to exclude duplicate publications, articles that did not fit the theme proposed, reviews, abstracts, graduation papers, dissertations, theses, and annals. Results: It was found 9 publications that fit the eligibility criteria and were used for the discussion process based and developed through the main nursing care to GBS carriers, using the systematization of nursing care (SAE). Conclusion: This research sought to answer the importance of nursing care provided to the patient with GBS done in a systematized way. The SAE proposes an optimal communication between the multidisciplinary health team which facilitates the recovery of the GBS patient.